IMPLEMENTATION OF PROJECT-BASED LEARNING (PjBL) MODEL IN IMPROVING CRITICAL THINKING SKILLS AND ABILITY TO COOPERATE IN PANCASILA EDUCATION CONTENT OF GRADE IV IN ELEMENTARY SCHOOL - Sari, Raihanah; Mutiani, Mutiani; Abbas, Ersis Warmansyah; Subiyakto, Bambang; Handayani, Mutia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
The investigation conducted points to empowering students to address issues concerning basic learning abilities and the ability to work together within the Pancasila Instruction content in primary schools. One of the arrangements for this issue is to utilize the Project-Based Learning (PjBL) model, which is integrated into the teaching and learning process. This research employs a quantitative approach and a qualitative approach in classroom activity research (CAR) exercises. The inquiry results showed that fundamental considering abilities, which received an evaluation of 90% with the criteria of